Capillary Force‐Driven, Hierarchical Co‐Assembly of Dandelion‐Like Peptide Microstructures. Issue 24 (10th March 2015) - Wang, Yuefei; Huang, Renliang; Qi, Wei; Xie, Yanyan; Wang, Mengfan; Su, Rongxin; He, Zhimin
<x xml:space="preserve">Abstract</x> The wetting and drying of drops on flexible fibers occurs ubiquitously in nature, and the capillary force underlying this phenomenon has motivated our great interest in learning how to direct supramolecular self‐assembly. Here, the hierarchical co‐assembly of two aromatic peptides, diphenylalanine (FF) and ferrocene‐diphenylalanine (Fc‐FF), is reported via sequential, combinatorial assembly. The resulting dandelion‐like microstructures have highly complex architectures, where FF microtube arrays serve as the scapes and the Fc‐FF nanofibers serve as the flower heads. Homogeneous FF microtubes with diameters tailored between 1 and 9 μm and wall thickness ranging from 70 to 950 nm are initially formed by controlling the degree of supersaturation of the FF and the water content. Once the FF microtubes are formed, the growth of the dandelion‐like microstructures is then driven by the capillary force, derived from the wetting and drying of the Fc‐FF solution on the FF microtubes. This simple and ingenious strategy offers many opportunities to develop new and creative methods for controlling the hierarchical self‐assembly of peptides and thus building highly complex nano and microstructures.